Transformasi Pembelajaran Bahasa Indonesia di Era Kecerdasan Buatan (Artificial Intelligence) - Uswatun Hasanah (Lentera: Jurnal Ilmiah Kependidikan, 2026)
The development of digital technology, particularly Artificial Intelligence (AI), has brought significant changes in various aspects of life, including the field of education. The utilization of AI provides new opportunities to create learning processes that are more innovative, effective, and adaptive to students’ needs. This study aims to examine the transformation of Indonesian language learning in the era of artificial intelligence and to explain the role of AI in supporting the learning process. The research method used is a literature review by examining various scientific sources such as journal articles, books, and conference proceedings related to the use of AI in education. The results of the study indicate that the implementation of AI in Indonesian language learning can improve the quality of learning through the use of various technologies such as chatbots, digital learning platforms, and automated evaluation systems that assist teachers and students in the teaching and learning process. In addition, AI also enables the creation of more interactive, flexible, and personalized learning according to students’ needs. However, the use of AI in education still requires supervision and wise utilization so that it does not reduce the important role of teachers as facilitators in the learning process. Therefore, the integration of artificial intelligence in Indonesian language learning needs to be continuously developed appropriately to improve the quality of education in the digital era.